Hypervalent Iodine(III) Reagent Mediated Regioselective Cycloaddition of Aldoximes with Enaminones. Issue 39 (14th October 2019) - Yoshimura, Akira; Jarvi, Melissa E.; Shea, Michael T.; Makitalo, Cody L.; Rohde, Gregory T.; Yusubov, Mekhman S.; Saito, Akio; Zhdankin, Viktor V.
Abstract : An efficient oxidative cycloaddition of enaminones with nitrile oxides generated in situ from respective aldoximes using hypervalent iodine reagents has been developed. Reactions of various aldoximes with enaminones in the presence of [hydroxy(tosyloxy)iodo]benzene involved the regioselective cycloaddition reaction resulting in the formation of the 3, 4‐disubstituted isoxazoles in moderate to good yields. Structures of several isoxazole products were confirmed by a single X‐ray crystallography. Abstract : Hypervalent iodine(III) reagent mediated regioselective cycloadditions of aldoximes with enaminones producing the 3, 4‐ or 3, 4, 5‐substituted isoxazole derivatives have been developed.